Sonographic Estimated Fetal Weight among Diabetics at ≥ 34 Weeks and Composite Neonatal Morbidity - Al-Hafez, Leen; Pirics, Michael L.; Chauhan, Suneet P. (American Journal of Perinatology Reports, 2018)
Objectives The objective was to assess the composite neonatal morbidity (CNM) among diabetic women with sonographic estimated fetal weight (SEFW) at 10 to 90th versus >90th percentile for gestational age (GA).Study Design The inclusion criteria for this retrospective study were singleton pregnancies at 34 to 41 weeks, complicated by diabetes, and that had SEFW within 4 weeks of delivery. Odds ratios (ORs) with 95% confidence intervals (CI) were calculated.Results Among the 140 cohorts that met the inclusion criteria, 72% had SEFW at 10th to 90th percentile for GA, and 28% at >90th percentile. Compared with women with diabetes with last SEFW at 10th to 90th percentile, those with estimate > 90th percentile for GA had a significantly higher rate of CNM (13 vs. 28%; OR, 2.65; 95% CI, 1.07–6.59). Among 109 diabetic women who labored, the rate of shoulder dystocia was significantly higher with SEFW at >90th percentile for GA than those at 10th to 90th percentile (25 vs. 2%; p = 0.002); the corresponding rate of CNM was 29 versus 10% (p = 0.02).Conclusion Among diabetic women with SEFW > 90th percentile for GA, CNM was significantly higher than in women with estimate at 10 to 90th percentile. Despite the increased risk of CNM, these newborns did not have long-term morbid sequela.
Keywords: diabetes; sonographic estimated fetal weight; composite neonatal morbidity